Klausula Baku dalam Perjanjian Asuransi Kecelakaan Diri pada PT. Asuransi Umum Bumiputera Muda 1967 dalam Transportasi Darat terkait Undang-Undang No. 8 Tahun 1999 tentang Perlindungan Konsumen - Djayanti, Achmad Busro, Suradi (Diponegoro Law Journal, 2013)
A standard Article in The Agreement of Accident Insurance of PT. Asuransi Umum Bumiputera Muda 1967 in Land Transportation Relates to Law Number 8 Year 1999 About Consumer Protection People in this universe always face some risks in their life, their family member or their properties. And it is kind of an uncertain risk. They always find the way to change that uncertainty of life to become something real or certain. One of the ways to undergo the risk is replacing it to another side , that is an insurance company. PT. Asuransi Umum Bumiputera Muda 1967 is an insurance company that is developing in Indonesia. It offers some insurance products, one of them is insurance for an accident of the people. It is packed into an attractive package “Paket Siagakoe”. Just like the other common agreements, PT. Asuransi Umum Bumiputera Muda 1967 uses a standard article in Agreement of Accident Insurance, it  gives the disadvantage to the consumer as an enduring person.The written of this law uses normative juridical approach method or usually called as doctrinal research (document study) where the secondary data which consists of primary, secondary and tertiary data becomes the source of it.The result of this research explains that founded many things in Agreement of Accident Insurance PT. Asuransi Umum Bumiputera Muda 1967 which are not appropriate with Law No. 8 Year 1999 about Consumer Protection, Section 8 subsection (1) and (2) so that it can damage the consumer as an enduring person.Some obstacles in implementation of accident insurance can be from the responsible person or enduring person. Obstacles occur because of the lack of communication and responsibility. They can be minimized by maximizing the duty of the agent, marketing staff in informing some important things in polis in the beginning and the end of the insurance, therefore in claim it can be beneficial for two sides especially the consumer.